Ta có: \(\overrightarrow {OA} + \overrightarrow {OB} = \overrightarrow 0 \Leftrightarrow - \overrightarrow {OA} = \overrightarrow {OB} \)
\(\Rightarrow {\overrightarrow {MO} ^2} - {\overrightarrow {OA} ^2} = \left( {\overrightarrow {MO} + \overrightarrow {OA} } \right)\left( {\overrightarrow {MO} - \overrightarrow {OA} } \right) \\= \left( {\overrightarrow {MO} + \overrightarrow {OA} } \right)\left( {\overrightarrow {MO} + \overrightarrow {OB} } \right) = \overrightarrow {MA} .\overrightarrow {MB} \) (đpcm)